PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN ORIENTASI KEWIRAUSAHAAN TERHADAP INTENSI BERWIRAUSAHA: (Studi Survei pada Siswa Kelas XII SMA Negeri 27 Garut) - Wida Mardiah; Tjutju Yuniarsih; Lili Adi Wibowo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine how the influence of entrepreneurial education and entrepreneurial orientation on entrepreneurial intention. This research method uses a correlation study with a quantitative approach. The subjects of this study were students of SMAN 27 Garut. The population in this study amounted to 124 students with a sample of 95 students. Analysis of the data in this study using SPSS 25. The results of this study indicate that students of SMAN 27 Garut have a high level of entrepreneurial education, have a high level of entrepreneurial orientation, and have a high level of entrepreneurial intention. The results of the data analysis of this study also show that entrepreneurship education has a significant effect on entrepreneurial intention and entrepreneurial orientation has a significant effect on students' entrepreneurial intentions